1992
DOI: 10.1111/j.1745-6584.1992.tb02004.x
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric and Aquifer Property Changes Above Subsiding Longwall Mine Panels, Illinois Basin Coalfield

Abstract: This study examined the response of potentiometric levels and hydraulic properties to subsidence caused by a 725‐ft‐deep active longwall mine in southern Illinois. The overburden is mainly shale but includes a shallow sandstone aquifer, overlain by a shale aquitard, capped by thin drift. Pumping and packer tests indicate that subsidence fracturing increased the hydraulic conductivities of the sandstone aquifer by about an order of magnitude, and of certain horizons of the lower bedrock by several orders. The w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…Subsidence was accompanied by considerable fracturing of the strata, particularly shear fractures in the marginal tension zones and vertical bedding separation in the central trough area. The hydrological effects of the subsidence have been reported by Booth & Spande (1992) and Booth et al (1997Booth et al ( , 1998.…”
Section: Jefferson County Sitementioning
confidence: 77%
See 1 more Smart Citation
“…Subsidence was accompanied by considerable fracturing of the strata, particularly shear fractures in the marginal tension zones and vertical bedding separation in the central trough area. The hydrological effects of the subsidence have been reported by Booth & Spande (1992) and Booth et al (1997Booth et al ( , 1998.…”
Section: Jefferson County Sitementioning
confidence: 77%
“…Previous studies (e.g. Hill & Price 1983;Walker 1988;Matetic & Trevits 1991Booth & Spande 1992) have demonstrated a typical response of rapid (but often temporary) decline in potentiometric heads, caused by the sudden increase in fracture porosity, and alteration of hydraulic gradients, caused by increased permeabilities. These effects are due primarily to in situ hydraulic property changes within the shallow bedrock aquifers, not to drainage into the mine.…”
Section: Description Of Longwall Subsidence and Its Hydrological Effectsmentioning
confidence: 96%
“…According to the analysis of key rock M of "step beam" structure in loading key strata, the discriminant of broken rock M in loading key strata when it does not appear downward sliding movement can be analyzed according to = 1.0 in formula (11). The condition which should be satisfied if rock M of "step beam" structure in loading key strata does not appear downward sliding movement is…”
Section: Movement Forms Of Overlying Strata and Formation Mechanism Omentioning
confidence: 99%
“…Calculated by formula (11), under different values of , if broken rocks of loading key strata do not appear downward sliding movement, the conditions which should be satisfied are shown in Figure 11(a). It is shown that it must meet the following condition: > 2.0 if the downward sliding movement of "step beam" structure does not occur.…”
Section: Movement Forms Of Overlying Strata and Formation Mechanism Omentioning
confidence: 99%
See 1 more Smart Citation